PERBEDAAN MORFOLOGIS POPULASI BOH A Botia macracantha ASAL SUMATERA DAN KALIMANTAN [Morphological differences among botia Botia macracantha populations originated from Sumatra and Kalimantan] - Sudarto Sudarto; Laurent Pouyaud (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2006)
There are two distinct morphological characters of Botia macracantha (Clown loach) originated from Sumatera and Kalimantan. It is assumed that those two populations caused difficulties in breeding program when the populations mixed up. To know the differences of those two populations at least 100 sampels were collected from Sumatra or 50 sampels of each location. Another location was West Kalimantan. Morfometric characters are measured among those populations and statistical analysis is implemented to know the differences among populations observed. The result showed that populations from Sumatra is differ morphometrically from Kalimantan.